The Relationship Between Adolescents' Personality and Neurasthenia: A Comparison of Australian and Chinese. (November 2019) - Ye, Lin; Zhu, Gu; Martin, Nick; Liu, Yangyang
The aim of the present study was to examine the cross-cultural differences in the relationship between personality traits and neurasthenia across early adolescence. The participants were from Australia and China. Adolescents' personality was measured by the Junior Eysenck Personality Questionnaire, and neurasthenia was measured by the Somatic and Psychological Health Report. Structural equation modeling showed that neuroticism significantly predicted neurasthenia for both Chinese and Australian adolescents. Multigroup comparisons indicated that the strength of the relationship between neuroticism and neurasthenia was consistent across Australian and Chinese adolescents. Our findings imply that the relationship between personality traits and neurasthenia is consistent across different cultures.